Utilizing Calcined Hard Clam Shells for Phosphate Removal Using an Up-flow Column Reactor Through Water Solution - Norzainariah Abu Hassan; Izzat Danial Mahadi; Nur Husna Muslim; Abdullah, Noorul Hudai; Nur Atikah Abdul Salim; Noraziah Ahmad; Wen-Pei Low (Journal of Advanced Industrial Technology and Application, 2025)
Phosphate pollution in aquatic environments is a critical environmental issue that poses a significant threat to water quality and the ecosystem, primarily from agricultural runoff, industrial discharges, and domestic wastewater effluents. This research aims to evaluate the effectiveness of calcining hard clam shells in phosphate removal and to understand the mass transfer process within an up-flow column reactor. Experimental data was analyzed using an up-flow column reactor to study the adsorption of phosphate deposited on the surface of calcined hard clam shells. According to preliminary findings, calcined hard clam shells show great potential for use as phosphate adsorbents due to their promising capacity and efficiency. The primary materials responsible for phosphate removal are calcium oxide (CaO) and calcium carbonate (CaCO?) generated through the calcination process, facilitating phosphate adsorption and precipitation. The analysis indicates that deeper adsorbent layers sustain better removal efficiencies throughout time. In contrast, shallower adsorbent layers approach solute saturation quickly through an up-flow column reactor. More extended periods of effective adsorption are provided by deeper adsorbent beds, according to the Bed Depth Service Time (BDST) model. These results are corroborated by the Thomas and Modified Mass Transfer Factor (MMTF) models, which demonstrate that while adsorption rates are higher in shallower beds, deeper beds have higher total capacities and longer service durations. This study contributes a thorough assessment of calcine hard clam shells as an affordable and environmentally friendly way to remove phosphate from wastewater, helping to reduce eutrophication in aquatic environments and improving tertiary wastewater treatment methods.